Infectious diseases and football - Lessons not only from COVID-19 - Duarte Muñoz, M.; Meyer, T. (Science and Medicine in Football, 2020)
The past few weeks have seen us make numerous and increasing adjustments to our regular schedules as the Corona virus (COVID-19) outbreak turned from an epidemic to a pandemic. Virtually every aspect of daily life has been influenced by preventive measures, the most notable of which is social distancing, and sporting events have not been an exception. In the case of football, this ended in the postponement of the EURO 2020, oneof the largest tournaments world-wide. However, this is not the first time that an outbreak occurs at an "inconvenient" time for football. In 2007 and 2008 a measles outbreak was noticed in Switzerland shortly before the 2008 European Football Championship11. A similar measles outbreak took place in 2009 in South Africa, before the start of the 2010 FIFA World Cup2,12 . In 2011, there was an endemic EHEC (entero-hemorrhagic E. coli) outbreak in Germany before the start of the Women`s World Cup. The 2014 FIFA World Cup in Brazil posed the risk of vector-transmitted diseases. During the tournament, Dengue risk would be close to its peak when matches were played in at least three cities: Fortaleza, Natal, and Salvador7. In this particular tournament, there were other mosquitotransmitted diseases, such as Zika and Yellow Fever, for which attendants and players had to take special precautions.